2021
DOI: 10.1155/2021/9937243
|View full text |Cite
|
Sign up to set email alerts
|

HuR Plays a Positive Role to Strengthen the Signaling Pathways of CD4+ T Cell Activation and Th17 Cell Differentiation

Abstract: After antigen and/or different cytokine stimulation, CD4+ T cells activated and differentiated into distinct T helper (Th) cells via differential T cell signaling pathways. Transcriptional regulation of the activation and differentiation of naïve CD4+ T cells into distinct lineage Th cells such as Th17 cells has been fully studied. However, the role of RNA-binding protein HuR in the signaling pathways of their activation and differentiation has not been well characterized. Here, we used HuR conditional knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Chellappan et al employed SRI-42127 to inhibit the nuclear shuttling function of HuR, thus suppressing its protein activity [ 40 ]. Additionally, some studies obtained HuR gene knockout cells from mice with conditional HuR gene deletion for subsequent experiments [ 41 , 42 ]. We leveraged the CRISPR/Cas9 gene-editing system to entirely and permanently ablate endogenous HuR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Chellappan et al employed SRI-42127 to inhibit the nuclear shuttling function of HuR, thus suppressing its protein activity [ 40 ]. Additionally, some studies obtained HuR gene knockout cells from mice with conditional HuR gene deletion for subsequent experiments [ 41 , 42 ]. We leveraged the CRISPR/Cas9 gene-editing system to entirely and permanently ablate endogenous HuR expression.…”
Section: Discussionmentioning
confidence: 99%
“…First, hY3 is part of ribonucleoprotein complexes and binds to proteins involved in mRNA processing and splicing, such as HuR (ELAVL1) [ 16 ]. Interestingly, HuR is involved in T cell activation response and differentiation [ 13 , 31 ]. Also, Karginov et al showed that HuR produced a broad control through upstream factors during T cell activation and that its depletion produced NFAT1 upregulation and NFAT2 downregulation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, MALT1 overexpression could result in kidney injury via activating nuclear factor κB (NF‐κB) signaling 15 . Additionally, it is illustrated that MALT1 enhances the differentiation of CD4 + T cells into Th1 and Th17 cells, meanwhile the differentiation of CD4 + T cells into Th1 and Th17, which are important in the pathology of sepsis 18–21 . However, the clinical relevance of MALT1 with sepsis, which is one of the most serious infection‐related diseases, still remains elusive.…”
Section: Introductionmentioning
confidence: 99%